2014
DOI: 10.2147/dddt.s63779
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine for acute bipolar depression: a systematic review and meta-analysis

Abstract: BackgroundPrecise estimated risks and benefits of quetiapine for acute bipolar depression are needed for clinical practice.ObjectiveTo systematically review the efficacy and the tolerability of quetiapine, either as monotherapy or combination therapy, for acute bipolar depression.MethodsWe included all randomized, controlled trials (RCTs) comparing quetiapine with other treatments, including placebo, in patients with acute bipolar depression (bipolar I or II disorder, major depressive episode). Published and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 28 publications
2
60
1
1
Order By: Relevance
“…The previous systematic review found that quetiapine monotherapy was an effective treatment in adult patients with bipolar depression,12 while our findings did not support those results. The different outcomes between adults and child and adolescent populations may be caused by either high comorbid psychopathology, such as attention-deficit hyperactivity disorder and conduct disorder,37 in children and adolescents with bipolar I or II disorder associated with poor response treatment or methodological limitations of the included studies 68…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The previous systematic review found that quetiapine monotherapy was an effective treatment in adult patients with bipolar depression,12 while our findings did not support those results. The different outcomes between adults and child and adolescent populations may be caused by either high comorbid psychopathology, such as attention-deficit hyperactivity disorder and conduct disorder,37 in children and adolescents with bipolar I or II disorder associated with poor response treatment or methodological limitations of the included studies 68…”
Section: Discussioncontrasting
confidence: 99%
“…Third, this review did not include patients with bipolar depression and disruptive mood dysregulation disorder diagnosed by using the DSM, Fifth Edition (DSM-5). Fourth, this review used narrow search terms as a previous review;12 therefore, the sensitivity of searching possibly decreased. Finally, selection, detection, and reporting biases of all the included studies were performed and the test of funnel plot to assess an asymmetry was unable to be carried out because of a limited number of eligible clinical studies 22.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-five reviews, including 179 trials with adult and 117 with pediatric participants, were finally analyzed (15, (Supplementary Table S1 online). From these reviews, 19 assessed the risk of bias (18,20,22,25,26,28,29,32,35,(37)(38)(39)(40)(41)44,46,(49)(50)(51), 6 reported only the Jadad score (15,19,21,36,45,48), 4 assessed only the allocation concealment (34,42,43,47), and 6 did not assess quality (23,24,27,30,31,33). Overall, 13 382 adult and 5 417 pediatric participants were enrolled in the placebo groups.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the clinical challenge that anxious bipolar depression presents, some positive findings exist in the literature. A review of 11 RCTs found that quetiapine (monotherapy or in combination) was associated with significant improvements in anxiety [measured by the Hamilton Anxiety Rating Scale (HAM‐A)] in bipolar depression . Similarly, patients with bipolar depression and high levels of anxiety (a score of ≥ 18 on the HAM‐A) experienced significant reductions in symptoms of both depression and anxiety following treatment with olanzapine or olanzapine–fluoxetine combination versus placebo; however, weight gain and increased cholesterol levels were also significant .…”
mentioning
confidence: 99%